Hubungan Pengetahuan Kesehatan Reproduksi Dengan Perilaku Seksual Remaja Di SMK BIM Banjarsari Kabupaten Lebak : The Relationship between Reproductive Health Knowledge and Adolescent Sexual Behavior at BIM Banjarsari Vocational School, Lebak Regency - Tisyawati, Herna; Anggraini, Nofa (Dohara POAJ, 2023)
Introduction: Sex education that is not given at an early age results in high levels of sexual violence against children committed by those closest to the child, including the family. This phenomenon shows the importance of understanding sex education in early childhood. The problem of sex education at this time is not being paid much attention to by parents, so they leave all their children's education to schools, including sex education. Even though those who are responsible for sex education in early childhood are parents, schools are only a complement, and in schools, there is no curriculum on sex education so early childhood is sometimes neglected. Methods: This research is quantitative research, namely research that uses data in the form of numbers as a tool to analyze information about what you want to know. Correlation research design with a cross-sectional approach. Results: In the chi-square test, the Asymptotic Significance (2-sided) value was obtained. The Pearson chi-square test obtained a p-value of 0,017 (< 0,05); so it can be concluded that H0 is rejected and Ha is accepted. Thus it can be interpreted that there is a relationship between respondents' knowledge and sexual behavior statistically and is quite significant for BIM Banjarsari Vocational High School students. Discussion: Reproductive health knowledge and social behavior of SMK BIM Banjarsari students is still lacking, there is a relationship between respondents' knowledge and sexual behavior statistically and quite significant for students of SMK BIM Banjarsari with a p-value of 0,017 (< 0,05).